Factorial Design Studies and Biopharmaceutical Evaluation of Simvastatin Loaded Solid Lipid Nanoparticles for Improving the Oral Bioavailability. (12th February 2014) - Krishnam Raju, Kovoru; Sudhakar, Beeravelli; Murthy, Kolapalli Venkata Ramana
Abstract : Statins are HMG-CoA reductase inhibitors, which lower the cholesterol level through reversible and competitive inhibition; they are involved in the biosynthesis of cholesterol and other sterols. Simvastatin exhibits poor oral bioavailability (<5%) and undergoes extensive microsomal metabolism by CYP enzymes. CYP3A4 is the major metabolizing enzyme that metabolizes lactone form of simvastatin and significantly lowers intestinal uptake. The hydrophobic properties of simvastatin prevent complete dissolution of the drug in the intestinal fluid which also contributes to its lower bioavailability. SLNs are alternative carrier system to polymeric nanoparticles. SLNs are in submicron size range (1–1000 nm). To overcome the hepatic first pass metabolism and to enhance the bioavailability, intestinal lymphatic transport of drugs can be exploited. In the present study, attempt has been made to prepare solid lipid nanoparticles of simvastatin to improve the bioavailability. SLNs of simvastatin were prepared with Trimyristin by hot homogenization followed by ultrasonication method. The SLNs were characterized for various physicochemical properties and analytical techniques like PXRD, DSC to study thermal nature and morphology of formulation and excipients. Promising results of the study indicated the applicability of simvastatin solid lipid nanoparticles as potential tools for improvement of bioavailability of poorly soluble drugs.